The Poor Widow’s Mites. A Contextual Reading of Mark 12:41-44 - Kubiś, Adam (The Biblical Annals, 2015)
An intriguing point of disagreement is evident among recent commentators on Mark 12:41-44 as to how we should understand the poor widow’s offering, whether as a positive or negative image. The crucial issue, raised for the first time by Addison G. Wright, is a proper grasp of the immediate narrative context of the poor widow’s story, which in his case produced the lamentable reading of the widow’s “deed.” Nevertheless, by widening the immediate narrative context and reading the account within the larger Markan framework, the interpretative ambiguity disappears. The widow is presented to Jesus’ disciples, and to the readers of the Markan story, as a positive example of selfdenial motivated by faith, love and devotion toward God. Thus, she not only stands as a symbol of the faithful remnant of Israel, but, most importantly, presents a picture of Jesus’ own self-offering on the cross.